Efficacy and safety of Hibiscus sabdariffa in cardiometabolic health: An overview of reviews and updated dose-response meta-analysis - Mostafa Norouzzadeh; Minoo Hasan Rashedi; Mohammad Hesam Azizi; Farshad Teymoori; Zohreh Maghsoomi; Farzad Shidfar (Complementary Therapies in Medicine)
Background: Conventional treatments for cardiometabolic diseases face limitations related to cost, efficacy, and side effects. Hibiscus sabdariffa (HS) is a common food product and a potential alternative. However, previous studies have shown inconsistent results and lacked assessments of result certainty, intervention safety, and subgroup analysis credibility. This study evaluated the efficacy and safety of HS on blood pressure (BP), lipid profiles, glycemic control, anthropometric parameters, inflammatory markers, oxidative stress indicators, and liver enzymes. Methods: To conduct this umbrella review, a systematic search of eligible meta-analyses was performed up to May 2024. The random-effects model was used to synthesize results from individual trials. Quality, certainty, and credibility of evidence were evaluated using the Cochrane Risk of Bias tool, AMSTAR-II, GRADE, and ICEMAN frameworks. Results: Data from 26 randomized controlled trials involving 1797 participants revealed that HS dose-dependently reduced systolic and diastolic BP compared to placebo and other teas. Although no significant differences were found between HS and antihypertensive drugs, HS showed moderate credibility for therapeutic BP reduction (> 10 mmHg), especially in individuals over 50 years, in trials lasting over four weeks, and in those with a low risk of bias. HS also reduced total cholesterol, LDL-C, fasting blood glucose, and increased HDL-C. A minor, clinically insignificant increase in aspartate aminotransferase was observed without elevating adverse event risks. Conclusions: HS showed BP-lowering effects comparable to antihypertensive drugs and beneficial impacts on lipid and glycemic profiles. Although HS is generally considered safe, long-term and therapeutic dosing safety requires careful monitoring.